Using composite system index to identify China’s ecological and socio-economic transition zone - Zhang, Hao; Liu, Fei; Zhang, Jinying (Frontiers in Plant Science, 2022)
Regions with synthetic geographical gradients tend to exhibit distinct ecological transitions. As a compound ecosystem, transition zone can provide a basis for decision-making in the sustainable ecological management by investigating its boundary and complexity. To determine the characteristics of the composite transition zone where natural ecological and socio-economic factors interact, a conceptual framework and a quantitative identification method for the ecotone of coupled human and natural systems have been proposed. The composite system index can be used to ascertain the coupling intensity, coupling direction, and ecological transition of the system. Taking China as an example, this study showed evidence of the existence of a tremendous amount of composite transition zone (complex coupled areas) between the east and west of China, and sporadic ecotone in other regions of the country. This composite transition zone accounted for about 1/4 of China’s land surface area, and had a fragile environment that faced challenges of environmental protection and economic development. In the area across the Hu Line, human and natural factors jointly explain a low proportion of the variance in composite transition zone (the complexity of coupled systems, with 62.01% of unexplained proportion higher than that in other regions). In this region, the topographic position index was the critical element associated with composite transition zone, and accounted for nearly 20% of the variation of composite system index. The discovery and characterization of the composite transition zone is crucial for understanding its uncertainty and diversity and the complex of coupled ecosystems.